Characterization and biological activity studies on some transition metal complexes of thiosemicarbazide derived from 2-picolinic acid hydrazide - Mohamed, Eshraga Eltayeb; AbedelKarim, Abeer Taha; Elmalik, Yahia Hassan; Mohamed, Amna Elamin; Aljahdali, Mutlaq Sheeded (European Journal of Chemistry, 2014)
Mixed-ligand bivalent transition metal ion complexes with N-ethyl-2-picolinoyl hydrazinecarbothioamide (EPHC) and 1,10-phenanthroline (1,10-phen) have been synthesized. The complexes namely [Cu(EPHC)(1,10-phen)(Cl)H2O] (1), [Ni(EPHC)(1,10-phen)(Cl)H2O] (2), [Mn(EPHC)(1,10-phen)(Cl)H2O] (3) and [Co(EPHC)(1,10-phen)(Cl)H2O] (4) were characterized by elemental analysis, spectral (IR, 1H NMR and UV-Vis) and magnetic moment measurements. The magnetic and spectral data indicates octahedral structure for all complexes. Metal complexes have been modeled using parameterized PM3 semi-empirical method. The free ligand and its M(II)-chelates have been screened for their antimicrobial activities. The antibacterial screening demonstrated that, the Cu(II) complex have the maximum and broad activities among the investigated complexes.